Pengaruh latihan senam aerobik terhadap kekuatan otot lengan, otot perut dan otot tungkai - Noortje Anita Kumaat, (Ilmu Keolahragaan, 2013)
Abstract : This study examined the effects of aerobic exercise training on muscle strength arm, abdomen and legs. The purpose of this study is to determine empirically the influence of the difference before and after aerobic exercise training to increase muscle strength arm, abdomen and legs. Population in this research is member or a member of Gymnastics SSFC Unesa. The number of samples taken were 25 people with a purposive sample. The method used in this study is to experiment with the design method pre test and post test group design. The number of samples consisted of one group.The data in this study was taken by using a push-up test instruments to measure arm muscle strength, sit ups to measure abdominal muscle strength and half Squat jump to measure leg muscle strength. After the data processing of descriptive data obtained as follows: 1.         In the variable arm muscle strength before the training given value:  = 11.86 and S = 5.52 and after the training given value:  = 16.06 and S = 5.37, and after the t test, t values obtained counting 14, 852 and t-table value = 2.064 (0:05:24). Because the value t count > t table is rejected and HA Ho accepted or there is a difference arm muscle strength before and after aerobic exercise training was given. 2.         In the abdominal muscle strength variables were given training before the value:  = 8.88 and S = 4.37 and after the training given value:  = 13.9 and S = 4.8 7, and after the t test, t values obtained counting 14.338 and t-table value = 2.064 (0:05:24). Because the value t count > t table is rejected and HA Ho accepted or there is a difference abdominal muscle strength before and after aerobic exercise training was given. 3.         In leg muscle strength variables were given training before the value:  = 1.56 and S = 4.5 and after the training given value:  = 17.76 and S = 4.89, and after the t test, t values obtained counting 22.122 and t-table value = 2.064 (0:05:24). Because the value t count > t table, so Ho rejected and HA received or there is a difference limb muscle strength before and after aerobic exercise training was given.   Key words : aerobics, arm muscle strength, abdominal, legs